PENGARUH INFLUENCER, MOTIVASI, DAN LITERASI KEUANGAN TERHADAP MINAT INVESTASI SAHAM DI KALANGAN MAHASISWA - Wulandari, Ni Putu Novi; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.07.TAHUN.2024DO - 10.24843/EEB.2024.v13.i07.p01, 2024)
Investment in the capital market can be used as an alternative investment for people who want to allocate their excess funds and at the same time act as a driver of economic growth in a country. The purpose of this research is to see the effect of influencers, motivation and financial literacy on the intention to invest in stocks. The research was conducted on active students of the Bachelor of Accounting Study Program batch 2019 and 2020 of the Faculty of Economics and Business, Udayana University who had taken capital market theory courses and obtained a total of 165 students. The sample selection method in this study was accidental sampling/convenience sampling. In conducting data analysis using multiple linear regression analysis with SPSS application tools. The results of the study reveal that influencer, motivation, and financial literacy positively influence interest in stock investment. This indicates that if the greater the influence of influencers on students, the interest of students to invest tends to increase, if the greater the influence of motivation on students, the greater the interest of students to invest, and if the ability of students' financial literacy increases, it will also increase interest in stock investment. tends to increase